Prolonged Apnea During Modified Electroconvulsive Therapy in a Patient of Suicidal Attempt by Organophosphorus Poisoning: A Case Report. Issue 2 (June 2016) - Dhakne, Rajesh; Mishra, Kshirod K.; Kumar, Vinay; Khairkar, Praveen
Abstract : Abstract: Organophosphorus (OP) pesticides are commonly used in agricultural fields to control pests in India. However, exposure to it can cause poisoning in humans and animals, or it can be taken intentionally as poison to commit suicide. We present a case of a 35-year-old suicidal man who developed prolonged apnea for almost 4 hours on day 13 of OP poisoning after brief general anesthesia induced by propofol and 1 mg/kg of suxamethonium, during the first session of the third cycle of modified electroconvulsive therapy, despite all due precautions. Such prolonged apnea secondary to complex interactions has been reported very rarely in literature. This case therefore, highlights the importance of careful evaluation and monitoring while giving anesthesia to OP-poisoning patients.